Electrochemical Synthesis of Imino‐C‐Nucleosides by "Reactivity Switching" Methodology for in situ Generated Glycoside Donors. Issue 17 (5th May 2021) - Okamoto, Kazuhiro; Tsutsui, Mizuki; Morizumi, Haruka; Kitano, Yoshikazu; Chiba, Kazuhiro
Abstract: Redox‐induced regioselective C(sp 3 )‐H C ‐glycosidation for unactivated prolinols was achieved by controlling the anomeric reactivity of electrochemically generated iminium cations. A mechanistic study revealed that the intermediate was pooled as covalent azaribose or iminium cation species in situ, and the electrophilicity of intermediates can be adjusted by changing coexisting acids. We found that the armed/disarmed analogy concept of traditional glycochemistry can be adapted to our C ‐glycosidation reaction. Finally, we invented a logical synthetic methodology, named "reactivity switching" concept, and synthesized a series of imino‐ C ‐nucleosides ( C ‐azanucleosides) based on this methodology. Abstract : Electrochemical C ‐glycoside formation was achieved by a "reactivity switching" methodology, which is an expansion of the traditional armed/disarmed concept. Logical reactivity design was enabled by considering electron density, p K a, and resulting anomeric leaving ability of acetate moiety of in situ generated glycoside donors. Finally, we synthesized various imino‐ C ‐nucleosides ( C ‐azanucleosides).